Learning Strategies and Technologies Applied by High Proficiency University Students for English as a General Subject - Sufiyandi Sufiyandi; Muhammad Fadhli; Ildi Kurniawan (Edukasi, 2021)
Learning strategy is an important factor in the success of achieving communicative language skills. Besides the awareness of using various strategies, applying technology in the language learning activity also becomes crucial for learners to succeed. However, learning strategies and the use of technologies by students of English Subjects at colleges and universities have not been widely found in the literature. For this reason, the research is aimed at finding out the application of strategies and technologies used by high proficiency students. The research is designed by combining both qualitative and quantitative research as the so-called Mixed Method. The participants involved were 33 high proficiency students in English subjects. They were taken based on the tests from 169 students spreading across four faculties at Universitas Bengkulu – Sumatera, Indonesia. After providing the test to determine the high proficiency student, the questionnaires were administered to collect the data related to the strategies and technologies applied by the students. Eventually, an interview was also undertaken to gain the qualitative data. Based on the questionnaire data, it was found that the students applied all learning strategies, namely: memory, cognitive, metacognitive, compensation, affective, and social strategies. Of the six strategies, metacognitive was the strategy mostly used with a mean score of 3.771 and followed by cognitive strategy with 3.643 points. Meanwhile, the least used ones were compensation and social, which have a value of 3.419 and 3.460, respectively. In addition, based on the interview, the use of technology as a learning strategy was also concluded. The high proficiency students applied various technologies such as mobile phones, various Internet Websites, and language applications to practice English. Of these various technologies, mobile phones were the most dominant.